1994
DOI: 10.1038/icb.1994.74
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of CD45R0 on natural killer (NK) cells in patients with an NK lymphocytosis

Abstract: Summary NK cells from three donors with a NK (CD3 -CD56 " CD 16 ") lymphoeytosis of unknown aetiology showed differential expression of CD45R0, an isoform of CD45 not expressed by NK cells from normal donors unless stimulated to proliferate in vitro. For donor FC, 60% of NK cells expressed CD45R0 over a 16 month period during which there was a partial resolution of the NK lymphoeytosis. For donor SW, 37% of NK cells expressed CD45R0. increasing to 87% over a 14 month period during which the NK lymphoeytosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The possibility that IL‐15 is involved in NK cell expansion in patients with chronic NK lymphocytosis has been suggested (Zambello et al , 1997b). However, the NK cells in patients with chronic NK lymphocytosis are quiescent and lack the markers (CD25, CD71) of proliferation (Warren et al , 1994). An alternative possibility is that the increased number of NK cells is maintained because normal apoptotic mechanisms are either inhibited, as suggested in the case of NK cell leukaemia (Mizuno et al , 1999), or defective, as suggested for T‐cell LGL leukaemias (Lamy & Loughran, 1999; Greer et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that IL‐15 is involved in NK cell expansion in patients with chronic NK lymphocytosis has been suggested (Zambello et al , 1997b). However, the NK cells in patients with chronic NK lymphocytosis are quiescent and lack the markers (CD25, CD71) of proliferation (Warren et al , 1994). An alternative possibility is that the increased number of NK cells is maintained because normal apoptotic mechanisms are either inhibited, as suggested in the case of NK cell leukaemia (Mizuno et al , 1999), or defective, as suggested for T‐cell LGL leukaemias (Lamy & Loughran, 1999; Greer et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…NK lymphocytosis patients and control subjects. Three patients (patients 1, 2 and 3) were part of an earlier study (Warren et al, 1994). In all patients, NK lymphocytosis was diagnosed as chronic and the condition stable for at least 1 year.…”
mentioning
confidence: 99%
“…Simultaneously, we observed a subpopulation of pleural NK cells expressing Toll-like Receptor 2 (TLR2), a molecule undetectable in resting NK cells but upregulated in response to IL-12 and protozoan glycolipids (Becker et al, 2003;Lindgren et al, 2010;Schierloh et al, 2007). Furthermore, we and others recently identified a subpopulation of pleural NK that down-modulates the CD45RA and up-regulates CD45R0 isoform, resembling the well known phenomenon that takes places during memory differentiation of T lymphocytes (Warren et al, 1994;Fu et al, 2011). Immunophenotypic analysis of peripheral blood (PB) and pleural fluid (PF) NK cells (CD56 + /CD3 -).…”
Section: Pleural Nk Cells Exhibit Activated Phenotypementioning
confidence: 87%